The Influence of Using Short Story Toward Students’ Vocabulary Mastery at the Seventh Grade Students of An’nur Junior High School Tanah Abang Jakarta Academic Year 2019 - 2020 - Febriyanti, Ega Dwi; Riandi, Riandi (Universitas Mathla'ul Anwar Banten, 2020)
As an International Language, English is important to learn by everyone in the world. The important thing which must mastery when someone learns English is vocabulary. As an important aspect, vocabulary is hard to master because the writing and the pronunciation is different and difficult to memorize. That’s why the researcher wants to develop a good teaching and technique to teach vocabulary mastery. The researcher also wants to steal interest of students then remove scared image of learn English using Short Story. Based on the explanation, the researcher purposed to investigate the influence of using short story toward students’ vocabulary mastery. The research used a quantitative method with true-experiment design. The researcher take two sample classes which 7-A as control class and 7-B as experiment class. After tested the validity of the instrument which used for the research, the researcher used 25 numbers of valid questions as the instrument. The researcher gives same pre-test for both of the sample class. Then the researcher gives “The Tortoise and The Hare” short story as treatment to experiment class. In the control class the researcher teach a using poetry “I Follow My Dreams By Delilah”. After treatment the researcher also gives both of the sample class same post-test. The test is contained of same question with the pre-test, but the researcher was mess up the number of question. After get the data of the research the researcher also analyzed the data. The result of the data shows the difference of score of the both of sample classes. The researcher found the score of experiment class is better than the control class. That can be seen as T-count 3.3153 > T-table 1.994. Based on the result of the research data above, Ho is rejected and Ha is accepted. The result also shows the significant increase of the score between pre-test and post-test of experimental class. And not any significant increase on the pre- test and post-test of control class. That mean, using short story to improved students vocabulary mastery is effective